2012
DOI: 10.1152/ajpendo.00516.2011
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic signaling and protein deposition are enhanced by intermittent compared with continuous feeding in skeletal muscle of neonates

Abstract: Orogastric tube feeding is indicated for neonates with impaired ability to ingest and can be administered by intermittent bolus or continuous schedule. Our aim was to determine whether feeding modalities affect muscle protein deposition and to identify mechanisms involved. Neonatal pigs were overnight fasted (FAS) or fed the same amount of food continuously (CON) or intermittently (INT; 7 × 4 h meals) for 29 h. For 8 h, between hours 20 and 28, pigs were infused with [(2)H(5)]phenylalanine and [(2)H(2)]tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 68 publications
7
74
1
Order By: Relevance
“…Recent findings in our neonatal piglet model have demonstrated that continuous feeding by orogastric tube reduces protein synthesis and blunts protein deposition compared with intermittent bolus feeding for 24 h (31,32,40). This reduced response to the same nutrient load is due to the relatively suppressed and constant hormone and substrate patterns incurred with continuous feeding that attenuate muscle protein synthesis.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Recent findings in our neonatal piglet model have demonstrated that continuous feeding by orogastric tube reduces protein synthesis and blunts protein deposition compared with intermittent bolus feeding for 24 h (31,32,40). This reduced response to the same nutrient load is due to the relatively suppressed and constant hormone and substrate patterns incurred with continuous feeding that attenuate muscle protein synthesis.…”
Section: Discussionmentioning
confidence: 88%
“…Proteins from LD muscle homogenates were subjected to Western blot analysis, as described previously (76 ; Cell Signaling Technology), total Deptor, mTOR, Raptor, Rictor, RagA, RagC, LAM-TOR1, and LAMTOR2 (Cell Signaling Technology), v-ATPase (V0d1 subunit; GeneTex, Irvine, CA), Rheb (R & D Systems, Minneapolis, MN), SLC38A9 (Antibody Verify, Las Vegas, NV), and GAPDH (Abgent, San Diego, CA). Blots were developed as described previously (31). Values for the protein phosphorylation were normalized by their corresponding protein abundance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,[11][12][13] Several studies have shown that intermittent bolus feedings reduce the time to achieve full enteral feeds, decrease feeding intolerance and increase weight gain, 14 but contrary results have also been published. 15 Feeding stimulates whole body protein synthesis in the human neonate.…”
Section: Resultsmentioning
confidence: 99%